Student Financial Literacy Determinants in Accounting Education: Faktor-Faktor yang Mempengaruhi Literasi Keuangan Mahasiswa dalam Pendidikan Akuntansi - Ika Supriyaningsih; Imelda Dian Rahmawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Financial literacy is an essential competency for individuals in managing personal finances and making informed economic decisions. Specific Background University students, particularly accounting students, are assumed to possess higher financial knowledge due to their academic exposure, yet empirical findings remain inconsistent. Knowledge Gap Previous studies show mixed results regarding the role of demographic factors in shaping student financial literacy, indicating the need for context-specific investigation. Aims This study examines the relationship between gender, parents’ socioeconomic status, and allowance with financial literacy among accounting students at Muhammadiyah University of Sidoarjo. Results Using a quantitative explanatory approach with 62 respondents, the findings reveal that gender, parents’ socioeconomic status, and allowance are not statistically associated with students’ financial literacy, either partially or simultaneously. Novelty This study provides empirical evidence that demographic characteristics do not necessarily differentiate financial literacy levels among accounting students within a local Indonesian university context. Implications The findings suggest that financial literacy development should prioritize experiential learning, behavioral aspects, and structured financial education rather than relying solely on demographic assumptions. Keywords: Financial Literacy, Accounting Students, Socioeconomic Status, Gender, Allowance Key Findings Highlights: Demographic characteristics do not differentiate literacy levels among accounting students. Parental background variables show no statistical association with financial knowledge. Financial understanding appears independent of monthly student spending capacity.